Adsorption Equilibrium for Heavy Metal Divalent Ions (Cu2+, Zn2+, and Cd2+) into Zirconium-Based Ferromagnetic Sorbent. (5th July 2017) - Lee, Agnes Yung Weng; Lim, Soh Fong; Chua, S. N. David; Sanaullah, Khairuddin; Baini, Rubiyah; Abdullah, Mohammad Omar
Abstract : Zirconium-based ferromagnetic sorbent was fabricated by coprecipitation of Fe 2+ /Fe 3+ salts in a zirconium solution and explored as a potential sorbent for removing the Cu 2+, Zn 2+, and Cd 2+ from aqueous solution. The sorbent could easily be separated from aqueous solution under the influence of external magnetic field due to the ferromagnetism property. A trimodal distribution was obtained for the sorbent with average particle size of 22.74  μ m. The –OH functional groups played an important role for efficient removal of divalent ions. The surface of the sorbent was rough with abundant protuberance while the existence of divalent ions on the sorbent surface after the sorption process was demonstrated. Decontamination of the heavy metal ions was studied as a function of initial metal ions concentration and solution pH. Uptake of the heavy metal ions showed a pH-dependent profile with maximum sorption at around pH 5. The presence of the ferromagnetic sorbent in solution at different initial pH has shown a buffering effect. Equilibrium isotherms were analyzed using Langmuir, Freundlich, Dubinin-Radushkevich, and Temkin isotherm models. Adequacy of fit for the isotherm models based on evaluation of R 2 and ARE has revealed that heavy metal ions decontamination was fitted well with the Freundlich model.